Integrating discrete event simulation and value stream map in improving body shop production performance - Azila-Nadiah, Dulli; Cheng, Jack Kie; Fazeeda, Mohamad (2016)
Value stream mapping (VSM) is a lean tool used to reflect the current state of an operation by visualizing the value added activities and widely used across industries. This study takes place in automotive industry which emphasizing on addressing waste that arise in the production. VSM is traditionally a powerful paper and pencil tool however, the static representation on the map urges the use of computer simulation as the complementary tool. DES is introduced to create dynamic on the VSM and addresses variability that exist in the system and to propose improvement design for the future state VSM.